Developing Children's Language Skills through Storybooks Based on Religious Moderation - Aprilian Ria Adisti; Sri Marwiyati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This research is a research and development that aims to produce children's story books based on religious moderation in order to develop language skills and to form a profile of Pancasila students in early childhood. This research started from the results of pre-research conducted through a survey which showed the fact that it was still rare to find references to teaching materials with special themes on religious moderation used in learning at Raudlatul Athfal. The research design uses the ADDIE model which consists of the Analyze, Design, Develop, Implement and Evaluate stages. The results showed that the product development of children's storybooks based on religious moderation is valid and feasible for use in PAUD learning. Moreover, the result also shows that this book has a real contribution to developing language skills in teaching religious moderation and shaping the character of early childhood in accordance with the profile of Pancasila students.